Efficiency Aspects of the Financing of Unemployment Insurance and Other Government Expenditure - Pissarides, Christopher A. (Review of Economic Studies, 1983)
This paper argues that if the disincentive effects of unemployment insurance result from higher reservation wages, they may be eliminated by financing benefits with a progressive income tax. The result is obtained within an equilibrium model with stochastic job matchings. An optimal tax formula is derived for a linear income tax, and shown to imply that the average tax rate should increase faster with income the higher the level of UI benefits relative to other government expenditure. In some cases optimal financing may require the subsidization of low-wage jobs.